EVALUASI SISTEM ONLINE SINGLE SUBMISSION RISK BASED APPROACH (OSS-RBA) DALAM PERIZINAN BERUSAHA DI DKI JAKARTA - Muhammad Alfin Syafiq Lubis; Augustin Rina Herawati (Journal of Management and Public Policy, 2026)
Business licensing services throughout Indonesia since 2021 are required to use the OSS RBA System in processing business permits. During the implementation of this national system, several problems have been found that are experienced by all users, including in the Province of DKI Jakarta, both in terms of system constraints, information, supporting services, and policy changes. This study aims to evaluate the OSS RBA System and analyze the challenges and drivers in the implementation of the OSS RBA System in DKI Jakarta. This study uses a qualitative-descriptive method and uses observation, literature study, and interviews with DPMPTSP DKI Jakarta and business actors who consulted regarding OSS RBA at DPMPTSP DKI Jakarta in collecting the data. This study uses the DeLone & McLean Information System Success Model (2003) to evaluate the OSS RBA System and identify the challenges and drivers in the implementation of the OSS RBA System. The results of the study found that the implementation of the OSS RBA System in DKI Jakarta excels in terms of service quality, basic information, general satisfaction, and net benefits, but needs to be evaluated regarding system quality and the provision of advanced information. The challenges include regulatory changes that still occur, the level of public understanding, and the escalation of problems to the central government, however strong and binding central government regulations and the supporting service programs provided become strong drivers. This study provides suggestions to BKPM and DPMPTSP DKI Jakarta as an evaluation of the implementation of the OSS RBA System to improve user convenience.